The repercussions of changing the personal status law on the increase in family lawsuits (Divorce and Khul' lawsuits as a model) - Allam, Abdelfattah Lotfi; Farah, Muhammad Saeid; Al-Khawaja, Muhammad Yasser; Elmesalamy, Marwa (Yayasan Mitra Persada Nusantara, 2023)
The current research dealt with the study of the impact of changing the Personal Status Law on the number of family lawsuits